Imperative function of electron beams in low-energy plasma focus device - Khan, M.Z.; Lim, L.K.; Yap, S.L.; Wong, C.S. (2015)
A 2.2 kJ plasma focus device was analysed as an electron beam and an X-ray source that operates with argon gas refilled at a specific pressure. Time-resolved X-ray signals were observed using an array of PIN diode detectors, and the electron beam energy was detected using a scintillator-assisted photomultiplier tube. The resultant X-rays were investigated by plasma focus discharge for pressures ranging from 1.5 mbar to 2.0 mbar. This range corresponded to the significant values of X-ray yields and electron beam energies from the argon plasma. The electron temperature of argon plasma at an optimum pressure range was achieved by an indirect method using five-channel BPX65 PIN diodes of aluminum foils with different thicknesses. X-ray yield, electron beam energy, and electron temperature of argon plasma were achieved at 1.5-2.0 mbar because of the strong bombardment of the energetic electron beam.